2016
DOI: 10.1002/anie.201603746
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Generation Non‐Covalent NAAA Inhibitors are Protective in a Model of Multiple Sclerosis

Abstract: Palmitoylethanolamide (PEA) and oleoylethanolamide (OEA) are endogenous lipid mediators that suppress inflammation. Their actions are terminated by the intracellular cysteine amidase, N-acylethanolamine acid amidase (NAAA). Even though NAAA may offer a new target for anti-inflammatory therapy, the lipid-like structures and reactive warheads of current NAAA inhibitors limit the use of these agents as oral drugs. Here, we describe a series of novel benzothiazole-piperazine derivatives that inhibit NAAA in a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…These include b-lactone, b-lactam, and isothiocyanate derivatives, which react covalently with the catalytic cysteine of NAAA (Alhouayek et al, 2015;Armirotti et al, 2012;Solorzano et al, 2009Solorzano et al, , 2010, and benzothiazole piperazine derivatives, which inhibit NAAA through a reversible noncovalent mechanism (Migliore et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These include b-lactone, b-lactam, and isothiocyanate derivatives, which react covalently with the catalytic cysteine of NAAA (Alhouayek et al, 2015;Armirotti et al, 2012;Solorzano et al, 2009Solorzano et al, , 2010, and benzothiazole piperazine derivatives, which inhibit NAAA through a reversible noncovalent mechanism (Migliore et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…FAAH is widely distributed (11) although it is most abundant in the brain and liver (12), whereas NAAA is almost exclusively expressed in immune cells (13,14) such as monocytes and tissue macrophages (15,16) but is also found in prostate epithelium (13,17). In light of the analgesic and antiinflammatory actions of PEA, multiple NAAA inhibitors have been developed over the last decade (18,19) and shown to exhibit beneficial effects in a range of rodent models of human disease, including inflammation (20)(21)(22)(23)(24)(25), allergic contact dermatitis (26), spinal cord trauma (27), neuropathic pain (28,29), chronic pain (30), inflammatory bowel disease (31), lung inflammation (25,32), arthritis (14), and multiple sclerosis (33).…”
mentioning
confidence: 99%
“…These properties are mediated by the activity of the FAAH substrate anandamide on cannabinoid receptors (18). Whereas FAAH hydrolyzes long-chain polyunsaturated NAEs, including anandamide, more efficiently than short unsaturated ones such as PEA (34), NAAA demonstrates an opposite substrate preference in vivo (27,28,31,33) and in vitro (35,36), with PEA being its optimal substrate (15,37). Another major difference between the two enzymes, besides tissue distribution, is their intracellular localization: FAAH is found in the cytosol tethered to the outer face of mitochondria and the endoplasmic reticulum (38), whereas NAAA is localized to acidic organelles such as the lysosome (16,37,39).…”
mentioning
confidence: 99%
“…Based on the structure of pyrrolidine derivatives, our research group identified a class of novel inhibitors with oxazolidone moiety, represented by F96 and F215, with nanomolar potency against NAAA (Yang et al, 2015;Li et al, 2017;Ren et al, 2017;Wu et al, 2019;Zhou et al, 2019). Migliore et al reported third-generation NAAA inhibitors based on a benzothiazole-piperazine scaffold that is stable in mouse plasma and liver microsomes (Migliore et al, 2016). Despite great efforts in the development of NAAA inhibitors, medicinal chemistry diversity has remained low.…”
Section: Discussionmentioning
confidence: 99%